Menganalisis Pernikahan Dini - Sayyidah, Nikum; Adelina, Sentia; R, Risalati; Hidayat, Riffal Chaerully (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Early marriage is certainly not a strange thing anymore, both in the mindset and views of society. early marriage often occurs at the age of 19 years and under, and early marriage is more dominant for women than men. Based on a survey conducted by researchers in Manalawangi Pandeglang, there are many different views from the community about early marriage, where early marriage is a topic that is often discussed by the community, due to several factors that occur in early marriage. The purpose of this research is to examine how the viewpoint of the people of Mandalawangi Pandeglang about early marriage and how the differences between communities with this phenomenon, as well as factors and what are the impacts that cause early marriage. The data collection techniques used are observation, interviews, and collecting scientific articles, journal books, and sources related to the topic of this research. The results of the research obtained regarding the community's perspective on the factors and impacts of early marriage in Pandeglang Mandalawangi Village show that the factors that cause early marriage are caused by environmental factors, family, economic factors, and their own will, while the impact is caused by psychology, health and economy.